Genetic analysis of an MDR-like export system: the secretion of colicin V. - Gilson, L (1990)
The extracellular secretion of the antibacterial toxin colicin V is mediated via a signal sequence independent process which requires the products of two linked genes: cvaA and cvaB. The nucleotide sequence of cvaB reveals that its product is a member of a subfamily of proteins, involved in the export of diverse molecules, found in both eukaryotes and prokaryotes. This group of proteins, here referred to as the 'MDR-like' subfamily, is characterized by the presence of a hydrophobic region followed by a highly conserved ATP binding fold. By constructing fusions between the structural gene for colicin V, cvaC, and a gene for alkaline phosphatase, phoA, lacking its signal sequence, it was determined that 39 codons in the N-terminus of cvaC contained the structural information to allow CvaC-PhoA fusion proteins to be efficiently translocated across the plasma membrane of Escherichia coli in a CvaA/CvaB dependent fashion. This result is consistent with the location of point mutations in the cvaC gene which yielded export deficient colicin V. The presence of the export signal at the N-terminus of CvaC contrasts with the observed C-terminal location of the export signal for hemolysin, which also utilizes an MDR-like protein for its secretion. It was also found that the CvaA component of the colicin V export system shows amino acid sequence similarities with another component involved in hemolysin export, HlyD. The role of the second component in these systems and the possibility that other members of the MDR-like subfamily will also have corresponding second components are discussed. A third component used in both colicin V and hemolysin extracellular secretion is the E. coli host outer membrane protein, TolC.